Geochemical Characteristics of the Jurassic Alkane Gas in the Muli Depression, South Qilian Basin: Implications for Potential of Light Oil and Condensate - Tan, Furong; Li, Yang; Xie, Zhiqing; Bian, Xiaowei; Du, Fangpeng; Liu, Shiming; Lu, Ping; Wang, Jingli (Frontiers in Earth Science, 2022)
The discovery of gas hydrates in the Muli Depression has made the South Qilian Basin (SQB) a hotspot for oil and gas exploration. Although many studies have been carried out on the gas hydrates, the geochemical characteristics have rarely been reported, which can effectively indicate the genetic type, diffusion, biodegradation, and thermal maturity of natural gas. In this contribution, the molecular composition and carbon isotopes of alkane gases were collected from gas hydrates and free gases in drilled boreholes of the Muli Depression. The results show that the majority of natural gases are oil-type gases, with a little coal-type gases. The natural gases have undergone biodegradation, leading to a decrease in the propane content and an increase in the methane content, with a heavier carbon isotope of propane and a lighter carbon isotope of methane. Some of the natural gases have experienced diffusion, resulting in a decrease in the methane content and an increasing value of Δ(δ13C1-δ13C2). Furthermore, the wet gases from natural gases were derived from the cracking of kerogen and crude oil at the thermal maturity stage. The dry gases in small quantities were produced by biodegradation of the wet gases. We propose that the potential for light oil and condensate exists in the Jurassic Yaojie Formation. Our new findings on the geochemical characteristics of natural gases provide new constraints for the study of petroleum systems and deeply buried sediments in the SQB.